Development and Evaluation of Vegan Yogurts and Sour Milk Alternatives from White Lupin (Lupinus albus L.) - Misz, András; Kocsubé, Sándor; Vágvölgyi, Máté; Bajzát, Judit; Vágvölgyi, Csaba; Csutorás, Csaba (Acta Biologica Szegediensis, 2024)
Cow milk allergy (CMA) triggers a clinically abnormal immunological response to cow milk proteins. To address this issue, extensive studies have explored milk alternatives from various animal and plant sources. This study introduces a method for producing white lupin milk, resulting in fermented dairy-like products (vegan yogurt and sour milk alternatives). Four commercial yogurt cultures, including two mesophilic (CHN-11, CHN-22) and two thermophilic (YC-380, YC-X11) mixed bacterial cultures, were tested, with thermophilic ones yielding superior sensory outcomes for lupin-based yogurt alternatives. Incorporating inulin (2%) enhanced sensory appeal, particularly evident in strawberry and peach-flavoured variants, which achieved sensory scores comparable to cow milk yogurts. Furthermore, white lupin-based yogurts demonstrated superior water-holding capacity (up to 47.11 g/100 g in comparison with 42.35 g/100 g measured for cow milk yogurt), influencing texture and mouthfeel. They also exhibited favourable fatty acid profiles, notably rich in beneficial unsaturated fatty acids such as linoleic and linolenic acid (up to 10.15% and 8.43%, respectively), indicating potential health benefits. Sensory evaluation underscored the impact of starter cultures on product attributes, with certain cultures yielding more favourable results. In conclusion, white lupin emerges as a promising alternative protein source with the potential to produce high-quality dairylike products. While white lupin-based products hold promise as functional foods for individuals with specific dietary needs, further research is necessary to address potential allergenic concerns associated with white lupin proteins.